Insurance Type and Access to Health Care Providers and Appointments Under the Affordable Care Act. Issue 2 (February 2018) - Alcalá, Héctor E.; Roby, Dylan H.; Grande, David T.; McKenna, Ryan M.; Ortega, Alexander N.
Abstract : Background: Millions of adults have gained insurance through the Affordable Care Act (ACA). However, disparities in access to care persist. Objective: This study examined differences in access to primary and specialty care among patients insured by private individual market insurance plans (both on-exchange and off-exchange) and Medicaid compared with those with employer-sponsored insurance. Research Design: Using data from the 2014 and 2015 California Health Interview Survey, logistic regression analyses were used to calculate the odds of being unable to access primary care providers, access specialty care providers and receive a needed doctor's appointment in a timely manner, with insurance type serving as the independent variable. Interaction terms examined if the expiration of the ACA's optional Medicaid primary care fee increase in 2014 modified any of these associations. Results: Findings showed poorer access to providers among those insured through Medicaid and the individual market (whether purchased through the state's health insurance exchange or off-exchange) relative to employer-based insurance. Poor access to primary care providers was seen among private coverage purchased via exchanges, relative to private coverage purchased on the individual market. In addition, findings showed that reduction of Medicaid fees coincided with reduced ability to see primary care providers. However, a similar trend was seen among those with employer-based coverage, which suggests that this change may not be attributable to reductions in Medicaid fees. Conclusion: Despite ACA-related gains in insurance coverage, those with on-exchange and off-exchange individual private insurance plans and Medicaid encounter more barriers to care than those with employer-based insurance. Abstract : Supplemental Digital Content is available in the text.